Foot Length for Gestational Age Assessment and Identification of High-Risk Infants: A Hospital-Based Cross-Sectional Study. (21st September 2021) - Tergestina, Mintoo; Chandran, Shanu; Kumar, Manish; Rebekah, Grace; Ross, Benjamin J
Abstract: The knowledge of the gestational age of the newborn is essential for management. In the absence of a dating scan, the postnatal assessment scores have drawbacks of being difficult to learn and administer in the community. The measurement of the foot length is easy, reproducible and offers an objective assessment. The objective of this study was to determine the correlation of postnatal (<48 h) foot length measurement (with calipers) with gestational age as determined by antenatal dating ultrasound, create a predictive model for the same and propose foot length measurement cutoffs for <37 and <34 weeks of gestation. Secondary objectives were to assess the correlation between foot length as measured with calipers and that measured with a ruler and a paper footprint. This was a hospital-based cross-sectional study. Among the 520 babies assessed, the correlation of foot length with gestational age was 0.89. Operational cutoffs for the categories of <37 and <34 weeks at a sensitivity of 95% were <70 and <65 mm, respectively. The Pearson's correlation between foot length as measured by caliper and ruler was 0.95 and between caliper and paper footprint was 0.87. This study correlating foot length and gestational age has the potential to help neonatal care providers make informed management decisions, particularly in resource-limited settings.